Associations Between Active Commuting and Sickness Absence in Finnish Public Sector Cohort of 28 485 Employees - Kalliolahti, Essi; Gluschkoff, Kia; Lanki, Timo; Halonen, Jaana I.; Salo, Paula; Oksanen, Tuula; Ervasti, Jenni (WILEY, 2025)
Active commuting can be beneficial for health. We examined whether active commuting by walking or cycling was associated with a lower risk of sickness absence in a Finnish public sector cohort of 28 485 employees. We used negative binomial regression to test associations of weekly active commuting in kilometers (no, low, moderate, and high dose) with all-cause sickness absence. Sickness absence data from employers registers comprised the number of (1) sickness absence days, (2) short (1-9 days) and (3) long (>= 10 days) sickness absence episodes during 12- and 24-month follow-ups. The models were adjusted for sociodemographic factors, lifestyle risk factors, and previous sickness absence. To demonstrate absolute risk, we calculated sex- and age-adjusted incidence for sickness absence per 100 person years for each active commuting exposure group. The associations of cycling and walking were additionally studied in separate analyses. Compared to passive commuters (no active commuting), high dose of active commuting (mean of 61 km/week) was associated with an 8%-12% lower relative risk of sickness absence days and an 18% lower relative risk of long episodes. The absolute rate of sickness absence per 100 person-years was up to 452 days and 10 long episodes lower in the high-dose active commuters group. In the further analyses separating cyclists and walkers, similar reduced risks were observed only among high-dose cyclists. Our findings suggest that regular active commuting by bicycle has potential for reducing sickness absence by reducing the risk of long sickness absence episodes.